Respuesta :

Answer:

-3

Step-by-step explanation:

Convert every fraction to an improper fraction just to make it easier.

43/10 - (12/5x + 11/2) = 1/2 (-18/5x + 6/10)

Distribute.

= 43/10 -12/5x - 11/2 = -18/10x + 6/10

Simplify using the common denominator, which is 10.

43/10 - 24/10x - 55/10 = -18/10 + 6/10

Isolate the x.

-24/10x + 18/10 = -43/10 + 55/10 + 6/10

Simplify.

-6/10x = 18/10

Multiply by the reciprocal (basically dividing fractions)

18/10 x -10/6

= -3

Answer:

x= -3

Step-by-step explanation:

43/10-12/5x-11/2=9/5x+3/5

-6/5=12/5x=-9/5x+3/5

-6-12x=-9x+3

-3x=9

x=-3